Cybersecurity military entities of the United States of America - Monika Pajurek (Facta Simonidis)
US armed forces have been operating in cyberspace for decades. Due to its position and highly developed digital infrastructure the United States are vulnerable to hackers. These attacks pose restrictions during military operations and can lead to the economic damage of the country. The article focuses on how the Pentagon perceives cybersecurity issues. Military cybersecurity entities include individual commands of the armed forces: USSTRATCOM, USCYBERCOM and Cyberspace Service Components. This article presents the military entities responsible for cybersecurity, pointing to their evolution and increasing importance in providing this kind of security for the country as well as on global scale.